Targeted treatment and survival in advanced non-squamous non-small cell lung cancer patients – a nationwide and longitudinal study - Nyen, Johanne Elise; Booth, Anja Ødegård; Husby, Øyvind; Bugge, Christoffer; Engebretsen, Ingrid; Oteiza, Francisco; Helland, Åslaug; Fjellbirkeland, Lars; Brustugun, Odd Terje; Grønberg, Bjørn Henning (Frontiers in Oncology, 2025)
ObjectivesWe aimed to describe treatment patterns, time on treatment (ToT) and overall survival (OS) for patients with advanced non-squamous, EGFR+, ALK+ and ROS1+ NSCLC in Norway.Materials and methodsWe extracted data on patients ≥ 18 years diagnosed with advanced non-squamous NSCLC between 2015 and 2022 from the Cancer Registry of Norway and data on cancer drug therapy from the Norwegian Patient Registry and the Norwegian Prescribed Drug Registry. ToT was measured from the date treatment was collected or administered until the last dispensing was depleted or last hospital drug administration. OS was measured from date of diagnosis until death.ResultsIn total, 5,279 patients were included, of whom 449 EGFR+, 131 ALK+ and 38 ROS1+. 75% of EGFR+ patients, 88% of ALK+ patients, and 58% of ROS1+ patients received at least one systemic treatment within the first three months after diagnosis. Median follow-up was 13, 19, and 4 months for EGFR+, ALK+, and ROS1+, respectively. The median ToT in first line (1L) for EGFR+ patients was 11 months for osimertinib (CI: 10.1-NA) and 9 months (CI: 8.2-11.2) for afatinib, dacomitinib, erlotinib and gefitinib. For ALK+ patients, median ToT in 1L was 20 months (CI: 14.7-23.7for alectinib, 11 months (CI: 4.7-NA) for brigatinib, and 7 months (CI: 2.9-21.6) for crizotinib. For the five ROS1+ patients treated with crizotinib in 1L, median ToT was 5 months (CI: 2.4-NA). For all patients with a targetable genomic alteration, unadjusted median OS was higher (p-value = 0.025) for patients diagnosed in 2020-2022 (median OS: 23 months, CI: 19.5-NA) compared to patients diagnosed in 2015-2019 (median: 19 months, CI: 16.5-21.2).ConclusionsToT for targeted therapies was shorter than progression-free survival in clinical trials. However, patients eligible for targeted therapy still had a survival improvement during the study period.